A building control point of view on demolition of full precast concrete buildings in Hong Kong / Kung Shu-hang, Raymond and Wu Po-tak, Alex - Kung, Shu-hang, Raymond; Wu, Po-tak, Alex (2012)
Five 16-storey precast concrete domestic buildings were constructed in 1967 at 6gau Tau Kok of Hong Kong to meet the demand for resettlement. Housing Department (HD) was established in 1973 and these blocks were under its administration which later became Lower 6gau Tau Kok Estate (L6TK). In 2010, HD decided to demolish L6TK for re-development. The demolition plans of the buildings were required to be submitted to the Independent Checking Unit (ICU) of HD for approval and to obtain the consent from ICU before demolition could be commenced. Demolition of full precast concrete high rise buildings had not been carried out in Hong Kong before so vetting of the demolition plans had to be continuously done in order to ensure the demolition work was safe. During the process of the demolition plans, ICU and project team exchanged views on the demolition methods and site trial was arranged. The demolition plans were approved on 3/9/2010 with appropriate precautionary measures introduced. The demolition of five precast concrete domestic blocks took 9 months to complete without accident. It is therefore worthwhile to share the experiences from building control point of view on the demolition of these full precast concrete buildings in Hong Kong.